Case Report: Diagnosis of Nocardia asteroides infection using metagenomic next-generation sequencing of lymph node puncture tissue - Yang, Ya Min; Guo, Jing; Dang, Ning Ning (Frontiers in Medicine, 2025)
The Nocardia genus is an aerobic, Gram positive, opportunistic pathogen that primarily affects cell-mediated immunosuppressed patients. The clinical manifestation of nocardiosis varies widely, making it challenging to diagnose. In this report, we describe a 48 year old woman with a muscular abscess caused by Nocardia asteroides. Venous blood, skin biopsy specimen, muscle tissue, and inguinal lymph node puncture tissue cultures yielded negative results. Using metagenomic next-generation sequencing (mNGS), the pathogen was identified as Nocardia asteroides. Whole-exome sequencing of the peripheral blood showed that the patient had a monoallelic mutation in the lipopolysaccharide-responsive beige-like anchor protein (LRBA) gene. The mNGS detected Nocardia asteroides in the patient, and the administration of accurate treatment led to her complete recovery.